BOARD DIVERSITY AND DISCRETIONARY ACCRUALS: A COMPARISON BETWEEN NIGERIA AND GHANA FAMILY-OWNED LISTED FIRMS (Journal of Global Accounting, 2025)
It is now an established concern in academic and professional discourses that majority ownership in family-owned firms confiscate the interest of the minority ownership. Therefore, the study examined and compared the effect of board diversity on discretionary accruals between Nigeria and Ghana family-owned listed firms. Sceondary data were sourced from the published annual financial reports of the concerned purposively selected 32 and four listed firms from the Nigerian Exchange Group and Ghana Stock Exchange market respectively. The study covered a seven-year period from 2017 to 2023. The inferential analysis was based on pooled ordinary least square and panel corrected standard error regression. The descriptive analysis results showed the presence of more discretional accruals practices among listed family-owned firms in Ghana than in Nigeria. Based on inferential analysis, aside structural diversity (board independence) that presents similar effects on discretional accrual in both countries, other two board traits such as female gender and educational background (financial expertise) present positive but different significant effects on discretionary accruals. Therefore, the study concluded that board peculiarities impact earnings quality (measured using discretional accrual) among listed family-owned firms in Nigeria and Ghana. Thus, inclusion of more female gender in the board of listed family-owned firms should be done with caution for long time sustainability of listed family-owned firms, while inclusion of more finance and account professionals in the board of the firms should be prioritised as a matter of policy.
Keywords: Board Diversity; Discretionary Accruals; Earnings Quality; Family Business; Financial Reporting Quality